2013
DOI: 10.1371/journal.pone.0074793
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Expression by Hodgkin-Reed-Sternberg Cells Is Associated with Reduced Overall Survival in Young Adult Patients with Classical Hodgkin Lymphoma

Abstract: Previous studies have investigated the prognostic relevance of MMP9 in classical Hodgkin lymphoma (cHL), with negative results. However, we have found that MMP9 immunoistochemical expression by Hodgkin-Reed-Sternberg cells is associated with reduced overall survival in a subset of young adult Brazilian patients diagnosed with cHL. Additionally, we have observed that MMP9 expression by neoplastic cells in cHL is associated with EBV positivity. These results may support a rational basis for additional studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Taken together, this suggests that IL-6 participates in the pathogenesis of HL. The another molecule, MMP9, enriched in the transcriptional misregulation in cancer pathway and was a hub protein in the PPI network in the present study, and has also been previously reported to be associated with reduced overall survival in patients with cHL ( 31 ) through effects on immune system regulation ( 32 ). A previous study has suggested that the patients with aggressive non-Hodgkin lymphoma and MMP9 expression had poor overall survival ( 33 ).…”
Section: Discussionsupporting
confidence: 72%
“…Taken together, this suggests that IL-6 participates in the pathogenesis of HL. The another molecule, MMP9, enriched in the transcriptional misregulation in cancer pathway and was a hub protein in the PPI network in the present study, and has also been previously reported to be associated with reduced overall survival in patients with cHL ( 31 ) through effects on immune system regulation ( 32 ). A previous study has suggested that the patients with aggressive non-Hodgkin lymphoma and MMP9 expression had poor overall survival ( 33 ).…”
Section: Discussionsupporting
confidence: 72%
“…Tissue microarrays (TMAs) and immunohistochemistry were done at the A. C. Camargo Cancer Center. The TMAs were built as reported elsewhere 32 . Each case was spotted in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…This relationship could be based on the differences in collagen metabolism in the qPET‐positive cases associated with poorer clinical outcome: an additional investigation revealed that the collagen modulating enzyme MMP9 was more expressed in the cases with an increased proportion of weakly stained fibers than in the cases with fewer such fibers. Increased MMP9 expression correlated with reduced overall survival in 148 young adult cases in one study 7 . Various other works indicated MMP9 as a correlate to collagen alteration in lymphomas 38–40 .…”
Section: Discussionmentioning
confidence: 84%
“…1,2,6 A potential histological parameter-the quantification of MMP9-positive cells-was currently discussed in several publications. [7][8][9] MMP9 is a matrixin belonging to the zinc-metalloproteinases family involved in collagenous degradation of the extracellular matrix. 10 The discovery of a robust and reliable prognostic marker would help especially in the selection of therapy for younger patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation